7th International Symposium on High-Temperature Metallurgical Processing : proceedings of a symposium sponsored by the Pyrometallurgy Committee of the Extraction and Processing Division (EPD) of the Minerals, Metals & Materials Society (TMS) held during TMS 2016, 145th Annual Meeting & Exhibition, February 14-18 Downtown Nashville, Tennessee, Music City Center /: proceedings of a symposium sponsored by the Pyrometallurgy Committee of the Extraction and Processing Division (EPD) of the Minerals, Metals & Materials Society (TMS) held during TMS 2016, 145th Annual Meeting & Exhibition, February 14-18 Downtown Nashville, Tennessee, Music City Center. (2016) - Unknown
No abstract available